Web -Based Online Library Management System at SMK Sultan Ismail, JB - Anis Nadiah binti Rahmat; Mohd Hamdi Irwan Hamzah (Applied Information Technology And Computer Science, 2021)
Abstract: Web-Based Online Library Management System at Sekolah Menengah Kebangsaan (SMK) Sultan Ismail, Johor Bahru (JB) is a system that helps students and teachers to manage school libraries more systematically and improve the weaknesses in the existing system. Therefore, this new system was developed to provide facilities for students and teachers to find out the status of books in the SMK Sultan Ismail Library by using this system which can be accessed via the internet. The methodology used in this system is the Waterfall model methodology. This system is developed using Visual Studio Code software, Xampp and also Windows 8 operating system in the system. In addition, teachers and students can also see the online catalogue included in the system.